2007
DOI: 10.1021/jo070477u
|View full text |Cite
|
Sign up to set email alerts
|

Bromination of Deactivated Aromatics: A Simple and Efficient Method

Abstract: Highly deactivated aromatic compounds were smoothly monobrominated by treatment with N-bromosuccinimide (NBS) in concentrated H2SO4 medium affording the corresponding bromo derivatives in good yields. Mild reaction conditions and simple workup provides a practical and commercially viable route for the synthesis of bromo compounds of deactivated aromatics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(36 citation statements)
references
References 39 publications
(27 reference statements)
0
36
0
Order By: Relevance
“…Among these reagents, N-bromosuccinimide (NBS) is a useful brominating reagent in laboratory synthesis, since only inert succinimide by-product formed in the process. A lot of methods have been developed for the preparation of aryl bromides from electron-rich aromatics, but the bromination of unactivated aromatics with NBS proceeded only in the presence of stoichiometric amounts of strong Lewis acids or protic acids as catalysts [7][8][9][10]. Moreover, harsh experimental conditions were required for the bromination of deactivated aromatics, such as high temperature and high acidic solutions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Among these reagents, N-bromosuccinimide (NBS) is a useful brominating reagent in laboratory synthesis, since only inert succinimide by-product formed in the process. A lot of methods have been developed for the preparation of aryl bromides from electron-rich aromatics, but the bromination of unactivated aromatics with NBS proceeded only in the presence of stoichiometric amounts of strong Lewis acids or protic acids as catalysts [7][8][9][10]. Moreover, harsh experimental conditions were required for the bromination of deactivated aromatics, such as high temperature and high acidic solutions [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…There are several halogenation methods available in literatures. [18][19][20][21][22][23] Some of the methods [18][19][20][21][22] were tried and did not introduce halogen only into the phenyl ring A of the final molecule PF-622. Krishna and her coworkers 23 reported that an aniline and anisole can be brominated by the electrophilic substitution of bromine-generated in situ from ammonium bromide as a bromine source and hydrogen peroxide as an oxidant.…”
Section: Resultsmentioning
confidence: 99%
“…This compound was prepared in four steps by bromination of 3-nitrobenzoic acid (12), [25] reduction of the carboxylic acid, [26] protection of the resulting alcohol as a MOM ether, [27] and a Bechamp reduction of the nitro group (Scheme 6). [28] The overall yield was 61 % over four steps.…”
Section: Resultsmentioning
confidence: 99%